1973
DOI: 10.1002/kin.550050314
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous gas‐phase pyrolyses with a wall‐less reactor. III. The oxygen–ethane reaction. A double reversal in oxygen and surface effects

Abstract: The impact of surface and oxygen on the oxidative pyrolysis of ethane at temperatures above 590°C was studied using a wall-less reactor. At very low conversions under homogeneous conditions, ethene formation begins at the same temperature regardless of whether oxygen is present or absent. Between 0.00 and 0.13% conversion (592-632"C), the rate with oxygen is actually less than the rate in the absence of oxygen. A reversal occurs at about 633°C above which oxygen has a promoting effect. It is concluded that und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Instead, a fraction of it speeds up homogeneous reactions. As argued previously, ,, oxygen is necessary in the gas phase to speed radical propagation reactions 50 and achieve quick ethylene formation, even though the main paths leading to ethylene are nonoxidative. Consistently, experiments showed that at the exit of the 1 cm long catalytic monolith, O 2 conversion and ethylene formation are not complete .…”
Section: Discussionmentioning
confidence: 81%
“…Instead, a fraction of it speeds up homogeneous reactions. As argued previously, ,, oxygen is necessary in the gas phase to speed radical propagation reactions 50 and achieve quick ethylene formation, even though the main paths leading to ethylene are nonoxidative. Consistently, experiments showed that at the exit of the 1 cm long catalytic monolith, O 2 conversion and ethylene formation are not complete .…”
Section: Discussionmentioning
confidence: 81%
“…The validity of this procedure has been repeatedly demonstrated. [8][9][10][11][12] In this manner a point sample taken at center stream at a specified distance from the injection tube is used to determine the concentrations of all reactants and products in that plane. The system is computerized such that the raw chromatographic data are converted directly to rate constants, activation energies, graphs etc.…”
Section: Methodsmentioning
confidence: 99%
“…As pointed out in the work of Taylor and Kulich (1973), O 2 is not involved in the initial stages of the process, until a pool of H radicals is formed (mainly via reaction 13). For this reason, the reaction of consumption of oxygen (step 14) is delayed with respect to ethane, and the formation of dehydrogenation products (that is, ethylene) occurs before the oxygenated ones (CO x ) The reactions of propagation occur with a significant rate via C 2 H 6 consumption, involving radical species, such as H · and OH according to step 15 and 16 As concerns the reactivity of the radicals in the consumption of C 2 H 6 to C 2 H 5 , it can be roughly ordered as follows: H > OH ≫ CH 3 > O.…”
Section: Discussionmentioning
confidence: 99%